Cellular Senescence as a Target in Cancer Control - Mar Vergel; Juan J. Marin; Purificacion Estevez; Amancio Carnero (Journal of Aging Research)
Somatic cells show a spontaneous decline in growth rate in continuous culture. This is not related to elapsed time but to an increasing number of population doublings, eventually terminating in a quiescent but viable state termed replicative senescence. These cells are commonly multinucleated and do not respond to mitogens or apoptotic stimuli. Cells displaying characteristics of senescent cells can also be observed in response to other stimuli, such as oncogenic stress, DNA damage, or cytotoxic drugs and have been reported to be found in vivo. Most tumors show unlimited replicative potential, leading to the hypothesis that cellular senescence is a natural antitumor program. Recent findings suggest that cellular senescence is a natural mechanism to prevent undesired oncogenic stress in somatic cells that has been lost in malignant tumors. Given that the ultimate goal of cancer research is to find the definitive cure for as many tumor types as possible, exploration of cellular senescence to drive towards antitumor therapies may decisively influence the outcome of new drugs. In the present paper, we will review the potential of cellular senescence to be used as target for anticancer therapy.